Vaginal Agglutination in a Postmenopausal Women – A Case Report - Rohina S. Aggarwal (Medical Science: Trends and Innovations Vol. 11, 2025)
This case report describes a rare instance of vaginal agglutination in a 65-year-old postmenopausal woman, a condition typically resulting from hypoestrogenism leading to adhesion and fusion of the vaginal walls. The patient presented with a six-month history of vaginal discomfort, dyspareunia, urinary difficulty, and a feeling of incomplete bladder emptying. Clinical examination revealed adhesion of the vaginal walls with a pinhole opening and atrophic epithelium, indicative of hypoestrogenism. A pelvic ultrasound and hormonal profile confirmed the diagnosis. Due to the extent of adhesions and symptoms, surgical intervention was performed under general anesthesia, where adhesions were carefully separated. Postoperative management included the use of a vaginal mold to prevent re-adhesion and a regimen of topical estrogen therapy to promote healing and epithelial regeneration. At the four-week follow-up, significant symptom improvement was noted, with no signs of re-adhesion and a more robust vaginal epithelium. Continued local estrogen therapy and periodic vaginal dilators were recommended. This case underscores the importance of considering vaginal agglutination in postmenopausal women with vaginal and urinary symptoms. When conservative treatments are insufficient, surgical intervention combined with postoperative estrogen therapy and mechanical dilation can effectively manage this condition, significantly improving the patient’s quality of life. Early recognition and appropriate management are crucial to prevent complications and ensure successful outcomes. This report highlights the need for heightened awareness among clinicians for prompt diagnosis and comprehensive treatment strategies.